An ectomycorrhizal nitrogen economy facilitates monodominance in a neotropical forest. (1st February 2016) - Corrales, Adriana; Mangan, Scott A.; Turner, Benjamin L.; Dalling, James W.
Abstract: Tropical forests are renowned for their high diversity, yet in many sites a single tree species accounts for the majority of the individuals in a stand. An explanation for these monodominant forests remains elusive, but may be linked to mycorrhizal symbioses. We tested three hypotheses by which ectomycorrhizas might facilitate the dominance of the tree, Oreomunnea mexicana, in montane tropical forest in Panama. We tested whether access to ectomycorrhizal networks improved growth and survival of seedlings, evaluated whether ectomycorrhizal fungi promote seedling growth via positive plant–soil feedback, and measured whether Oreomunnea reduced inorganic nitrogen availability. We found no evidence that Oreomunnea benefits from ectomycorrhizal networks or plant–soil feedback. However, we found three‐fold higher soil nitrate and ammonium concentrations outside than inside Oreomunnea ‐dominated forest and a correlation between soil nitrate and Oreomunnea abundance in plots. Ectomycorrhizal effects on nitrogen cycling might therefore provide an explanation for the monodominance of ectomycorrhizal tree species worldwide.